MATERIAL SELECTION AND ORBITAL MANEUVER DESIGN FOR SOLAR SAIL TO EXPLORE THE OUTER SOLAR SYSTEM - Wahyudi, Oqely
This research is motivated by the success of several spacecraft missions using Solar Sail propulsion such as IKAROS, Lightsail, and others. This is due to the development of technology to create lightweight, thin, and strong materials such as aerogel, graphite, carbon foam, etc. Each material has several parameters, such as strength, absorbance, transmissivity, and reflectivity coefficient when interacting with photons. These parameters produce complex dynamics that need to be simulated to maximize the force of the Solar Sail. This research has several stages. The first stage is to learn about the types of light and strong materials and the optical parameters of materials from several literatures. The second step is to calculate the forces acting on the Solar Sail due to photons. The third stage is to determine the relationship of the force due to the photon with the central force of the Sun. The fourth stage is to simulate several orbital maneuvers and visualize them. Software used on this stage is Jupyter Notebook and Matlab. The equations used are Newton's laws of motion and gravity, also laws of radiation (black body radiation). This research also uses several numerical methods such as Runge-Kutta-Verner and Bisection method. The results show that of the various types of materials used, it is evident that the graphite+molybdenum material which has the characteristics with the highest acceleration is used as a Solar Sail material to maneuver to the outer Solar System with a minimum distance of 0.015 au from the Sun. Furthermore, the force generated by the point source model can be used as an approximation for r ? 1 au from the Sun. Meanwhile, for r < 1 au, the extended+limb darkening source model is used to increase the accuracy of the force. The Solar Sail with ???? = 0.01 kg/m2 has a final speed of 65 - 134 km/s (13.73 - 28.39 au/yr) depending on the final aphelion point (raf) selection. Solar Sail with a target Kuiper Belt object (30 - 60 au) has a traveling time of 3.4 - 4.4 years and a target SGL (Solar Gravitational Lens) with a traveling time of 17 years. The Solar Sail with ???? = 0.001 kg/m2 has a final speed of 32.15 - 413.96 km/s (6.783 - 37,389 au/yr) depending on maneuver selection and can go to SGL with a traveling time of 6.89 years. Based on the research that has been done, it can be concluded that the planets play a significant role in the orientation of the spacecraft's orbit, but the final velocity is not that significant.